Fuzzy modelling of static system optimum traffic assignment problem having multi origin-destination pair - Temelcan, Gizem; Kocken, Hale Gonce; Albayrak, Inci (ELSEVIER SCIENCE INC, 2021)
Traffic congestion is an unpreventable problem to avoid in a transportation network and it has negative effects on traffic accident, time wasting, traffic delay and safety problem. Besides, in transportation networks, drivers do not want to deal with traffic jam while traversing between specified origin-destination pair. Therefore, traffic assignment (TA) is imperative to improve traffic management, transportation safety, time, and cost savings. System Optimum Traffic Assignment Problem (SOTAP) is a kind of TA model which aims to minimize the total system travel time on the network, and satisfies the flow conservation constraints. To model the SOTAP more realistically, the imprecise parameters can be taken as fuzzy. Therefore, in this paper, we focus on converting the conventional SOTAP to a fuzzy quadratic programming problem (QPP) which is named System Optimum Fuzzy Traffic Assignment Problem (SOFTAP). Here, link travel time is expressed with BPR function as generally used in the literature by converting to fuzzy except link-dependent parameters. Thus, the nonlinear objective function of SOFTAP is expressed in terms of fuzzy link flows and fuzzy link travel times. A solution approach from the literature is modified to the reconstructed SOFTAP.
Keywords: SOTAP; BPR function; Triangular fuzzy numbers; Fuzzy QPP; LINEAR-PROGRAMMING PROBLEMS; TRAVEL-TIME FUNCTIONS; ALGORITHM; CHOICE; NETWORKS; DEMAND; Business & Economics; Operations Research & Management Science